PERAN SANKSI PAJAK, MODERNISASI PELAYANAN PAJAK, PEMAHAMAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Wijaya, Aillen Cindy Clara Jofan; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2025)
This research was conducted with the aim of knowing the effect of tax sanctions, modernization of tax services, and understanding of taxes on individual taxpayer compliance in DKI Jakarta. The sample was selected by purposive sampling method and valid data were 80 respondents. The data processing technique uses multiple linear regression analysis assisted by the SPSS (Statistical Product and Service Solution) program for Windows released 20 and Microsoft Excel 2013. The results of the research conducted show that there is a significant positive effect between tax sanctions, service modernization and tax understanding on taxpayer compliance. The implication of this research is that it is necessary to increase the firmness of sanctions, services that utilize technology and public understanding in an effort to increase taxpayer compliance.